ECG features and proarrhythmic potentials of therapeutic hypothermia. Issue 19 (20th May 2016) - Lee, Woo Seok; Nam, Gi-Byoung; Kim, Sung-Hwan; Choi, Jin Hee; Jo, Uk; Kim, Won Young; Oh, Yong-Seog; Park, Kyu Nam; Seo, Guang-Won; Kim, Ki-Hun; Jin, Eun-Sun; Rhee, Kyoung-Suk; et al.
Abstract : Objective: Hypothermia can induce ECG J waves. Recent studies suggest that J waves may be associated with ventricular fibrillation (VF) in patients with structurally normal hearts. However, little is known about the ECG features, clinical significance or arrhythmogenic potentials of therapeutic hypothermia (TH)-induced J waves. Methods: We analysed ECGs from 240 patients who underwent TH at six major university hospitals in Korea between August 2010 and December 2013. The prevalence, amplitudes and distributions of the J waves and the development of malignant arrhythmia were analysed. Results: The average patient body temperature was 33.5±1.0°C during TH. J waves were observed in 98 patients (40.8%). They were newly developed in 91 cases, and pre-existing J waves were augmented in seven patients. J waves during TH were primarily observed in leads II, III, aVF and V4–6 . The average amplitude of the J waves was 0.239±0.152 mV. There were four VF events during TH. These events occurred in three patients who were finally diagnosed with Brugada syndrome, idiopathic VF or early repolarisation syndrome, respectively, and in one patient with non-cardiac aetiology (asphyxia). Conclusions: J waves were recorded in about 40% of the patients who received TH. They were most frequently observed in the inferior limb leads or lateral precordial leads. Life-threatening VF occurred only rarely (1.7%) during TH and were mainly observed in patients with primary arrhythmic disorder. Although a causal relationship between TH-induced J waves and VF remains unknown, administering TH to this potentially susceptible, high-risk population may require careful attention.